Biomarkers detection on hydrogenated graphene surfaces : towards applications of graphane in biosensing - Tan, Shu Min (2013)
Graphane, the hydrogenated form of graphene, is a material of significant interest. Here we compare properties of hydrogenated graphene and ordinary graphene used for electrochemical oxidation of important biomarkers, such as ascorbic acid, dopamine and uric acid.